YUK TANI: Optimizing the Distribution of Agricultural Products through Android-Based Applications - Oktavia, Chaulina Alfianti; Meisaroh, Firda; Abdillah, Rizky (Economics and Business Journal (ECBIS), 2024)
The Pajarakan District area is an agricultural area where 61% of the area is rice fields. Even though the Pajarakan Subdistrict area has large agricultural land, it does not make farmers feel benefited when the harvest season arrives, because many of the farmers feel at a loss because their crops are bought by collectors at low prices. The purpose of this research is to create a system for selling agricultural products to help farmers sell agricultural products directly to agents in order to get a higher price than the price of collectors. In this study, a system was successfully created with the name YUK TANI based on Android using Android Studio, and the CodeIgniter 4 framework for creating REST APIs, and MySQL as database storage. With this system of selling agricultural products, it is hoped that it can help farmers in the Pajarakan District area to improve their economy when post-harvest arrives.